2022
DOI: 10.3390/antibiotics11060722
|View full text |Cite
|
Sign up to set email alerts
|

Sarecycline Demonstrates Clinical Effectiveness against Staphylococcal Infections and Inflammatory Dermatoses: Evidence for Improving Antibiotic Stewardship in Dermatology

Abstract: Tetracycline class antibiotics are widely used for multiple skin diseases, including acne vulgaris, acne rosacea, cutaneous infections, inflammatory dermatoses, and autoimmune blistering disorders. Concerns about antibiotic resistance and protecting the human/host microbiome beg the question whether broad-spectrum tetracyclines such as doxycycline and minocycline should be prescribed at such a high rate by dermatologists when a narrow-spectrum tetracycline derivative, sarecycline, exists. We evaluated the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…Due to the dramatically reduced side effects, we deduce that OMC is promising for the treatment of RGM infections. Unfortunately, although the best safety parameters were obtained for SAC in this study and in other reports, SAC demonstrated only mild inhibitory activity against the RGM strains ( 38 , 39 ). A clinical phase II trial including 285 subjects showed that once-daily oral treatment with SAC was safe and well tolerated at a dosage of 3.0 mg/kg of body weight for 12 weeks.…”
Section: Discussioncontrasting
confidence: 46%
“…Due to the dramatically reduced side effects, we deduce that OMC is promising for the treatment of RGM infections. Unfortunately, although the best safety parameters were obtained for SAC in this study and in other reports, SAC demonstrated only mild inhibitory activity against the RGM strains ( 38 , 39 ). A clinical phase II trial including 285 subjects showed that once-daily oral treatment with SAC was safe and well tolerated at a dosage of 3.0 mg/kg of body weight for 12 weeks.…”
Section: Discussioncontrasting
confidence: 46%
“…These antibiotics can cause tinnitus, pseudotumor cerebri, or vertigo with the latter adverse event leading to restrictions on minocycline use in military aviators [ 37 , 44 ]. Minocycline can cross the blood–brain barrier, potentially explaining the increased risk for dizziness and vertigo [ 43 , 45 ]. Although topical minocycline has a low resistance claim on its label, oral minocycline does not.…”
Section: Other Negative Effects Of Traditional Tetracycline Usagementioning
confidence: 99%
“…Furthermore, it has been demonstrated from X-ray crystallography that the unique chemical group, the carbon 7 (C7) moiety, on sarecycline is critical for establishing biochemical properties for sarecycline that distinguish it from doxycycline and minocycline. These structural and biochemical differences are directly related to sarecycline’s decreased propensity for inducing antibiotic resistance, as illustrated by sarecycline’s increased ability to cause steric clash with the ribosomal protection protein TetM ( Figure 3 ) [ 45 , 53 ].…”
Section: Benefits Of Sarecycline: Reduced Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Although exhibiting good activity against RGM, OMC and ERC showed poor or mild activity against MAC and M. kansasii (OMC against MAC: MIC 50 = >16 μg/mL, MIC 90 = >16 μg/mL; OMC against M. kansasii : MIC 50 = 8, MIC 90 = 16 μg/mL; ERC against MAC: MIC 50 = >8 μg/mL, MIC 90 = >8 μg/mL; ERC against M. kansasii : MIC 50 = 1 μg/mL and MIC 90 = >8 μg/mL) 5,8 . SAC showed mild inhibitory activity against RGM, whereas the activity of SAC against SGM has not been reported to date 9 . In addition, SGM isolates were limited in the previously mentioned studies, and no study has been conducted on SGM isolates in China.…”
Section: Introductionmentioning
confidence: 96%